CPIA Africa, July 2018 : Assessing Africa's Policies and Institutions - World Bank Group (World Bank, Washington, DC, 2018)
Favorable global economic conditions supported a turnaround in economic activity in Sub-Saharan Africa in 2017, easing pressure on weak policy frameworks. Output growth rebounded to an estimated 2.6 percent after decelerating to 1.5 percent in 2016 amid challenging external and domestic conditions. Notwithstanding the recent upturn in economic activity, growth remained well below its pre–financial crisis average of around 5 percent; moreover, per capita growth was negative for a second consecutive year. Important near and longer term vulnerabilities remain in many of the region's economies: eroded policy buffers constrain the scope for countries to formulate an adequate policy response to adverse shocks; public debt relative to gross domestic product (GDP) is rising, with implications for debt sustainability; employment opportunities severely lag the growing labor force, and livelihoods and economic fortunes are still tied to commodity price shocks and production disruptions, underscoring the limited economic diversification in the region; and poverty is widespread.